Does adolescent obesity affect surgical presentation and radiographic outcome for patients with adolescent idiopathic scoliosis?. Issue 1 (January 2017) - Bjerke, Benjamin T.; Saiyed, Rehan; Cheung, Zoe B.; Uppstrom, Tyler J.; Shifflett, Grant D.; Cunningham, Matthew E.
Abstract : The purpose of this study was to test a hypothesis that overweight patients with adolescent idiopathic scoliosis present with larger curves and achieve less surgical correction than do healthy weight counterparts. A total of 251 individuals were grouped by BMI into overweight (BMI% ≥85) and healthy weight (BMI% <85) groups. Overweight patients demonstrated significantly larger intraoperative blood loss ( P =0.041), although there was no significant difference in the number of intraoperative transfusions. Major curves and surgical correction were similar between the two groups. A greater postoperative thoracic kyphosis at latest follow-up may suggest a worsening sagittal profile in these individuals postoperatively.